Implementing mhGAP training to strengthen existing services for an internally displaced population in Pakistan - Humayun, A. (Glob Ment Health (Camb), 2017)
BACKGROUND. In 2014, over a million people were internally displaced after the launch of a military operation in North Waziristan, a tribal region on Pakistan's side of the Durand Line. Despite security concerns and restrictions, a collaborative mental health and psychosocial support initiative was undertaken in the district of Bannu. Monthly mental health camps were conducted for a period of 6 months by a multidisciplinary mental health team. The initiative also helped to assess mental health needs and plan training for primary care staff to strengthen existing resources. METHODS. As part of this initiative, Mental Health Gap Action Programme (mhGAP) training was conducted for physicians and psychosocial staff in the affected district. This marked the first instance of implementing these guidelines in Pakistan following a humanitarian crisis. This paper describes the training process including the adaptation of the mhGAP curriculum, training of trainers, training workshops for primary care staff and an analysis of results of pre- and post-testing of their knowledge about common mental disorders using a 25-item questionnaire. RESULTS. The gaps in knowledge of primary care physicians in recognizing and managing common mental disorders were clearly identified. The mean pre- and post-test scores of the participants were 15.43, 62% (p value 0.000, s.d. 4.05) and 19.48, 78% (p value 0.000, s.d. 3.13) respectively, which showed significant improvement. CONCLUSIONS. Despite the challenges of a humanitarian crisis, mhGAP guidelines can be successfully implemented to train primary care physicians in in low- and middle-income countries such as Pakistan. However, the dearth of primary care resources can hinder the complete integration of mental health services into primary healthcare.